2020
DOI: 10.3390/molecules25143125
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimycobacterial Activity and Physicochemical Characterization of Diaryl Ether Triclosan Analogues as Potential InhA Reductase Inhibitors

Abstract: Two sets of diphenyl ether derivatives incorporating five-membered 1,3,4-oxadiazoles, and their open-chain aryl hydrazone analogs were synthesized in good yields. Most of the synthesized compounds showed promising in vitro antimycobacterial activity against Mycobacterium tuberculosis H37Rv. Three diphenyl ether derivatives, namely hydrazide 3, oxadiazole 4 and naphthylarylidene 8g exhibited pronounced activity with minimum inhibitory concentrations (MICs) of 0.61, 0.86 and 0.99 μg/mL, respectively comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Moreover, based on available IC 50 and MIC (for standard and clinical S. aureus MRSA strains) values, the selectivity index (SI) was calculated for several compounds as the IC 50 /MIC ratio (Table 5). 60 Within the group of most active compounds ( 6 , 12 , 20 , 22–24 ), SI values were generally higher than 10, indicating their potential as antibacterial agents with respect to S. aureus MRSA.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, based on available IC 50 and MIC (for standard and clinical S. aureus MRSA strains) values, the selectivity index (SI) was calculated for several compounds as the IC 50 /MIC ratio (Table 5). 60 Within the group of most active compounds ( 6 , 12 , 20 , 22–24 ), SI values were generally higher than 10, indicating their potential as antibacterial agents with respect to S. aureus MRSA.…”
Section: Resultsmentioning
confidence: 96%
“…The selectivity index (SI) was calculated as , in accordance with previously described protocols. 60 …”
Section: Methodsmentioning
confidence: 99%
“…We previously reported on the preparation of 4-iodobenzohydrazide [ 15 ], and we also used the procedure for 2-phenylacetohydrazide [ 16 ], [1,1’-biphenyl]-4-carbohydrazide [ 17 ], 4-phenoxybenzohydrazide [ 18 ], 4-(trifluoromethoxy)benzohydrazide [ 19 ], 3-(trifluoromethyl)benzohydrazide [ 20 ], 2-(trifluoromethyl)benzohydrazide [ 21 ], 4-(hydrazinecarbonyl)benzenesulfonamide [ 22 ], 4-cyanobenzohydrazide [ 23 ] and 4-(trifluoromethyl)benzenesulfonylhydrazide [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The InhA active site involves the substrate binding loop (SBL: residues 197-226) as well as the NAD cofactor that interacts with the protein and the acyl substrate (or inhibitors) (26,27) . The InhA inhibitors include prodrugs such as INH which irreversibly interact with NAD forming an adduct (28) , direct inhibitors like triazoles, diphenyl ethers, and triclosan involved in reversible binding to the NAD (29)(30)(31) , or bulky inhibitors displacing the NAD like pyridomycin (32) . Literature reports revealed that Tyr158 and Phe149 are the two key amino acids involved in the binding interactions (33) .…”
Section: Enoyl Acyl Carrier Protein Reductase (Inha Enzyme) As a Main...mentioning
confidence: 99%